2019
DOI: 10.3390/en12142661
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Thermal and Electrical Characteristics of an Air-Based Photovoltaic Thermal Collector

Abstract: A photovoltaic thermal (PVT) system is a technology that combines photovoltaics (PV) and a solar thermal collector to produce thermal energy and generate electricity. PVT systems have the advantage that the energy output per unit area is higher than the single use of a PV module or solar thermal collector, since both heat and electricity can be produced and used simultaneously. Air-based PVT collectors use air as the heat transfer medium and flow patterns are important factors that affect the performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Kim et al suggested a newly designed air-type PVT collector, which has bending round-shaped heat-absorbing plates and experimentally investigated the electrical and thermal characteristics. In this study, it was observed that thermal and electrical efficiencies improved as the air mass flow rate was raised [1]. Choi et al suggested a PVT air collector that employed a non-uniform transverse rib and double-flow air channel.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Kim et al suggested a newly designed air-type PVT collector, which has bending round-shaped heat-absorbing plates and experimentally investigated the electrical and thermal characteristics. In this study, it was observed that thermal and electrical efficiencies improved as the air mass flow rate was raised [1]. Choi et al suggested a PVT air collector that employed a non-uniform transverse rib and double-flow air channel.…”
Section: Introductionmentioning
confidence: 78%
“…It can directly change incident solar radiation into electrical power. However, only around 12-18% of solar radiation turns into useful electrical energy during the operation of the PV module [1]. Much solar irradiance captured by a PV module is reflected or changed into thermal energy that leads to high increases in the temperature of the PV module.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the PVT collectors with and without triangular obstacles are modeled based on the simple thermal circuit model reported and used in previous studies similar to the present work [16,[33][34][35][36]. performance, and they reported that the suggested PVT collector had thermal and electrical efficiencies of 29-42% and 15.71-16.25%, respectively [29]. Choi et al evaluated the performance of a PVT collector coupled with a triangle-shaped obstacle located at the bottom of the air duct, experimentally, in the actual weather condition [30,31].…”
Section: Theoretical Model Of the Air-cooled Pvt Collectormentioning
confidence: 95%
“…Moreover, this method has benefits in manufacturing and price because of its simple design. Kim et al proposed a PVT collector with a round heat-absorbing plate in an air channel and experimentally investigated its performance, and they reported that the suggested PVT collector had thermal and electrical efficiencies of 29-42% and 15.71-16.25%, respectively [29]. Choi et al evaluated the performance of a PVT collector coupled with a triangle-shaped obstacle located at the bottom of the air duct, experimentally, in the actual weather condition [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…When air passes through the PVT collector from the inlet to the outlet, the absorber plates lengthen the airflow pathway and create turbulence inside the collector. The lengthened air pathway and turbulence both help to increase heat transfer and improve the thermal performance of the PVT collectors [19]. The designed BIPVT collectors were connected to a direct expansion air handling unit (AHU) and installed in an experimental house.…”
Section: Experimental House Of the Ahu System With Bipvt Collectormentioning
confidence: 99%